Undervalued tuna meat (Thunus obesus and Katsuwonus pelamis lineaus) to develop sausages - Salazar, Diego; Salinas , Daniel; Gallegos , Lilián; Moreno, Mishell; Sánchez-Moreno, Hugo; Pérez , Lander (Vitae, 2024)
Background: The tuna industry is one of the most essential sectors in global food production. Nevertheless, commercial meat known as "tuna loin" holds the utmost significance in producing and marketing its various products. Regrettably, fractions like tail and head meat have been overlooked and wasted due to their comparatively lower commercial value. Despite possessing notable technological value, this meat is typically reutilized into animal feed through flour production, missing the chance to create alternative high-value food products. Objective: This study aimed to develop and evaluate the sausages produced with the underutilized cuts of tuna (tail and head meat). Methods: The tuna utilized were Big-eye (Thunus obesus) and Skip-jack (Katsuwonus pelamis lineaus). Three (3) different types of sausages were formulated using 100% of Big-eye (BE), 100% of Skip-jack (SJ) tuna meat, and 100% of beef/pork meat (Control). The sausage pH changes during storage at 4 ± 1oC were analyzed and compared with the control. Proximal, microbiological, and sensory characteristics were evaluated. Results: The pH of sausages showed that the values tended to decrease in control, while this value increased in two types of tuna. The formulated tuna sausages yielded 72% moisture, 18% protein, 4.1% lipid, 0.4% ash, 0.4 % fiber, and 4.5% carbohydrates. Sensory attributes showed excellent acceptance regarding color, smell, flavor, and texture. Overall acceptability was qualified as "liked," and the acceptability index ranged from 76% to 86%. During the refrigeration storage, the microbiological analyses indicated that the total coliform count was < 3 CFU/g. Escherichia coli, Staphylococcus aureus, and mesophilic aerobic bacteria in tuna sausage showed absence during 24 days of storage. Conclusion: Using tuna tail and head meat enabled the development of gel-type emulsified products (sausages) that exhibited good nutritional, sensory, and microbiological quality.